2019
DOI: 10.4081/ripppo.2019.348
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of alliance ruptures in the psychotherapy of adolescents with borderline personality pathology: timing, typology and significance

Abstract: Jeremy Safran and his research group suggest that rupture-repair processes are important for the therapeutic change in patients with personality disorders. In this exploratory study, we describe alliance ruptures and resolutions on a session-by-session basis in a clinical sample of adolescents with Borderline Personality Pathology (BPP). Three research questions are addressed: i) Is there a typical trajectory of alliance ruptures over treatment time? ii) Which rupture and resolution markers occur frequently? i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 58 publications
(85 reference statements)
3
38
0
Order By: Relevance
“…As a sidenote, and to put previous findings in this sample into perspective, in a previous study on silence in psychotherapy, we showed that in the present sample, silence can be problematic for the psychotherapeutic process ( Zimmermann et al, 2020 ). A further study based on the same data showed that there is an increased risk of withdrawal ruptures ( Schenk et al, 2019 , 2020 ) during psychotherapy in youth with BPD. We believe that these phenomena (silence and ruptures) are part of the normal psychotherapeutic process but that they imply a risk of being detrimental to the psychotherapeutic process because they can rigidify the interaction and hinder synchronization of the dyad in a larger sense.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…As a sidenote, and to put previous findings in this sample into perspective, in a previous study on silence in psychotherapy, we showed that in the present sample, silence can be problematic for the psychotherapeutic process ( Zimmermann et al, 2020 ). A further study based on the same data showed that there is an increased risk of withdrawal ruptures ( Schenk et al, 2019 , 2020 ) during psychotherapy in youth with BPD. We believe that these phenomena (silence and ruptures) are part of the normal psychotherapeutic process but that they imply a risk of being detrimental to the psychotherapeutic process because they can rigidify the interaction and hinder synchronization of the dyad in a larger sense.…”
Section: Discussionmentioning
confidence: 85%
“…There are several psychotherapeutic approaches specifically developed for adolescent with BPD: e.g., dialectical behavior therapy for adolescents (DBT-A; Fleischhaker et al, 2011 ), mentalization-based treatment for adolescents (MBT-A; Rossouw and Fonagy, 2012 ), adolescent identity treatment (AIT; Foelsch et al, 2014 ), and schema-focused psychotherapy for adolescents ( Loose, 2015 ). The therapeutic process with BPD patients is often challenging because symptoms of BPD (e.g., rejection sensitivity) can hinder the construction of a good therapeutic relationship ( McMain et al, 2015 ) through an increased risk of ruptures of the therapeutic alliance ( Schenk et al, 2019 , 2020 ). Psychotherapy process research investigates active ingredients of therapeutic interventions and helps improve therapeutic approaches, as well as informing psychotherapists about the mechanisms of change and how they may leverage these actions ( Hardy and Llewelyn, 2015 ; Zimmermann et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The summing of these events by session can only provide an idea of an overall effect (which would not as such be reflected in a single event). The problem could be attenuated by correlating silence with significant therapeutic events such as ruptures and resolutions or change moments (Krause et al, 2007; Schenk et al, 2019; Zimmermann et al, 2018), thus narrowing down the meanings of silence episodes to more specific contexts. In addition, the definition of silence as absence of speech for at least 3 s is arbitrary and was based on existing literature (Daniel et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Pre-post analyses showed that 39.3% of the patients were remitted by the end of treatment, in addition to significant improvements on a range of other measures. Likewise, Schenk et al ( 2019 ) conducted a small exploratory study of psychodynamic therapy, involving 10 adolescents (aged 14–18) with identity diffusion and BPD symptoms. Results showed a significant reduction in psychopathology and an improvement in psychosocial functioning over time.…”
Section: Resultsmentioning
confidence: 99%